Indicadores de desenvolvimento rural da população dos municípios do oeste Paranaense: uma metodologia de estudo - Thomas, Jorge André (2015)
The purpose of this study was to identify the degree of rural development of the population of municipalities in the west of Paraná, evaluating four aspects: population, social welfare, economic performance and environment, based on the indicators proposed by Kageyama (2004) and to identify the environmental awareness and consumption behavior of family farmers in the municipality of Marechal Cândido Rondon, state of Paraná, with the methodology VAPERCOM of Brandalise (2008). To reach the purpose, it was held an exploratory research, having as procedures the literature research for the secondary data collection. The primary data were obtained through adjustments of the model from Kageyama and Brandalise, with an approach to the problem by mixed methods. This study is justified by the fact that those already made on the subject don t dealt with the paranaense west region and there is a gap regarding the assessment of the environmental variable and on this, it was conducted an applied research with family farmers the city of Marechal Cândido Rondon, state of Paraná, intending to contribute to the academic community and the public sector, providing information that could help in the formulation of public policies and the evaluation of the goals of rural development. As a result, the 50 municipalities of the paranaense west, 13 have an high IDR, 12 municipalities a Medium IDR I, another 12 with Medium IDR II and finally, 13 municipalities with Low IDR. The degree of perception and behavior of consumption of family farmers in the municipality of Marechal Cândido Rondon, state of Paraná demonstrates an environmental concern at all stages of the product life cycle. It is considered that the methodology proposed at this study, fills the gap of Kageyama s study (2004), wherein, this method was adapted, as well as at VAPERCOM s model, from Brandalise (2008), consisting of an evolution from both methods. The research instrument created for this purpose, meets these criteria, it assesses in greater detail each step of the product life cycle, that is, from production to disposal